ALETRNATIF PENYELESAIAN SENGKETA DALAM SENGKETA TRANSAKSI ELEKTRONIK (E-COMMERCE) - Salami, Rochani Urip; Bintoro, Rahadi Wasi (Faculty of Law, Universitas Jenderal Soedirman, 2013)
In e-commerce transactions in cyberspace it is possible occur a dispute as well as dispute occur within a legal relationship which is done conventionally. The more numerous and widely distributed activities of trade, then the frequency of occurrence of dispute be high and it means there'll be a dispute that must be solved. Dispute resolution itself basically qualifying to dispute resolution by peaceful and dispute resolution in adversarial. Resolving disputes peacefully is better known with concensus. While the dispute resolution in adversial, better known as resolution of disputes by a third party who is not involved in the dispute. The form of peaceful dispute resolution is negotiation, mediation and conciliation, while resolution form adversial is through the courts or the arbitral institutions. Dispute resolution in accordance with the philosophy of the inception of e-commerce is through negotiation, mediation, conciliation and arbitration.Keywords: e-commerce, dispute, dispute resolution, alternative dispute resolution